Pengaruh Daya Tarik, Fasilitas dan Harga Tiket terhadap Kepuasan Pengunjung Objek Wisata Bukit Holbung di Kabupaten Samosir - Josua May Rio Putra Pakpahan; John Sihar Manurung (JURNAL RISET MANAJEMEN (JURMA), 2024)
One of the mainstay tourist attractions in Samosir Regency is Holbung Hill. There are several factors that are the reason tourists visit a tourist attraction, including attractiveness, facilities and ticket prices. A tourist attraction is a place with beauty, uniqueness, authenticity and value that can be used as a place of entertainment for tourists in an effort to fulfill their spiritual and physical needs. Facilities are everything that is provided to be used and enjoyed by visitors while using the services so as to make visitors feel comfortable. The ticket price is the amount charged for a service in order to obtain the benefits of the service. Tourist visits that do not experience a significant and unstable increase are phenomena in this study. The research aims to determine the effect of attraction, facilities and ticket prices on visitor satisfaction at the Bukit Holbung tourist attraction in Samosir Regency. This research was conducted using a quantitative approach. The object of research is visitors to the Holbung Hill tourist attraction in Samosir Regency in 2022. The population in this study is unknown. The sample in this study was 100 visitors. Data collection was carried out using a questionnaire via Google form and observation at tourist destinations. Data analysis used is validity test, reliability test, classic assumption test, multiple linear regression and hypothesis testing. The results showed that visitor satisfaction at the Bukit Holbung tourist attraction in Samosir Regency was significantly and partially influenced by attractiveness, facilities, and ticket prices. Simultaneously attractiveness, facilities and ticket prices have a positive and significant effect on visitor satisfaction. Attractiveness has the most dominant influence on visitor satisfaction. The multiple linear regression equation for this study is Y = 1.667 + 0.267X1 + 0.366X2 + 0.251X3 + e. The test results of the coefficient of determination show that all the variables of attractiveness, facilities and ticket prices are able to explain 74.5% and the remaining 25.5% are influenced by other variables not examined in this study.